Risk-Bearing and the Theory of Income Distribution - Banerjee, Abhijit V.; Newman, Andrew F. (Review of Economic Studies, 1991)
This paper develops the stochastic theory of distribution with a dynamic model which focuses on the role of incomplete insurance in generating inequality. Unlike previous work, our approach takes explicit account of the reason for market incompleteness in modeling agents' behaviour; in particular, the amount of risk borne is endogenous. Using a model of growth with altruism in which agents are risk-averse and there is moral hazard, we show that lineage wealth follows a Markov process which converges globally to an ergodic distribution; this also represents the long-run population distribution of wealth. We discuss the role of particular assumptions, such as availability of production loans and unboundedness of utility, in yielding the qualitative properties of the distribution of wealth, the choice of “occupation” and the prevention of poverty traps.